Photovoltaic modules designed for architectural integration without negative performance consequences. - López-Escalante, María Cruz; Navarrete-Astorga, Elena; Gabás-Pérez, Mercedes; Ramos-Barrado, José Ramón; Martín-Jiménez, Francisco de Paula (My University, 2020)
Nowadays, the photovoltaic technology level development makes it the best option for its building integration as energy supplier. Nevertheless, its aesthetic appearance plays a relevant role because architect requirements go beyond the simple installation of solar devices on terraces. In order to fulfill their requirements, the typical white backsheet uses to be replaced by a black one. This simple change leads to a huge PV module performance reduction. In this work, it has been demonstrated that a suitable material selection allows to fabricate photo voltaic modules with a high architectonic integration, but without power reduction with respect to the most commercial solar devices. The former consists in the replacement of the typical glass front cover and the white backsheet by an antireflective glass and a black backsheet respectively. All the study has been developed on real size photovoltaic modules fabricated in an automatic line. The obtained results determine that those modules where black backsheets are used, suffer a power reduction equal to 8.66 W per fabricated module. Nevertheless, when in addition of the black backsheet an antireflective coating glass is implemented, the resulted PV modules present a more aesthetic presence without a detrimental of their power performance when they are compared to the standard PV modules. Additionally, the fabricated solar devices using the proposed configuration successfully overcome the most common aging tests.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/11131
Keywords: Instalaciones fotovoltaicas; Architectural integration; Power balance; Novel material design; Silicon photovoltaic module; Antireflective coating; Black backsheet